Quantitative phase-field model for phase transformations in multi-component alloys - Choudhury, Abhik Narayan (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2013)
Phase-field modeling has spread to a variety of applications involving phase transformations.While the method has wide applicability, derivation of quantitative predictions requires deeper understanding of the coupling between the system and model parameters. The book highlights a novel phase-field model based on a grand-potential formalism allowing for an elegant and efficient solution to problems in phase transformations.